Double-homozygosity for Factor V Leiden and Prothrombin c.*97G > A Mutation in a Young Female with Recurrent Fetal Losses and no Venous Thromboembolism - Ibrahim Abukhiran; Judy Jasser; Sharathkumar Bhagavathi (Elsevier, 2020)
Factor V Leiden (FVL) and factor II c.*97G > A mutation are the two most common genetic factors predisposing to hereditary thrombophilia. Being extremely rare, it used to be thought that double homozygosity for both variants is inconsistent with life. Only two cases describing double-homozygous patients with venous thrombosis were reported about two decades ago. However, to the best of our knowledge, there has been no reported case of double-homozygous individuals presenting with recurrent fetal losses rather than venous thrombosis. Herein, we present the case of a 36-year-old female who presented with recurrent first trimester miscarriages without developing venous thromboembolism. Testing with allele-specific polymerase chain reaction showed double-homozygous pattern for both FVL and factor II c.*97G > A mutation, both of which were confirmed by next generation DNA sequencing. With a population prevalence of less than one per ten million individuals, double-homozygotes' actual increase in risk for venous thromboembolism or fetal loss is unknown.